Pengembangan Bahan Ajar Menulis Cerita Rakyat Bermuatan Kearifan Lokal Sumatera Utara Berbantuan Media Komik Digital Untuk Siswa - Santa Hoky Hutagalung; Mara Untung Ritonga; Wisman Hadi (Varied Knowledge Journal, 2026)
This study aims to describe the development process, assess the feasibility, and determine the effectiveness of teaching materials for writing folklore integrated with the local wisdom of North Sumatra and supported by digital comic media for seventh-grade students at SMP Negeri 1 Pasaribu Tobing. The study employed the Research and Development (R&D) method using the ADDIE model, which consists of the stages of Analysis, Design, Development, Implementation, and Evaluation. The development process began with a needs analysis involving teachers and students, followed by the design phase, development of learning materials and digital comic media, expert validation, implementation, and product evaluation. The validation results indicated that the teaching materials were categorized as highly feasible, with material expert assessments ranging from 93.9% to 95.1%, design expert assessment at 94.8%, and Indonesian language teacher assessment at 95%. The trial results showed very positive student responses, reaching 91.6% in the small-group trial and 92.7% in the large-group trial. The effectiveness of the teaching materials was demonstrated by the improvement in students’ learning outcomes after using the developed product. In addition to enhancing students’ folklore writing skills, the teaching materials also promoted the values of North Sumatran local wisdom, such as Dalihan Na Tolu, marsiadapari, holong, mutual cooperation, responsibility, and respect for others. Therefore, the developed teaching materials were found to be highly feasible and effective for use in Indonesian language learning.